Circular RNA hsa_circ_0003574 as a biomarker for prediction and diagnosis of ischemic stroke caused by intracranial atherosclerotic stenosis - Li, Lingfei; Si, Xiaoli; Ruan, Jie; Ni, Zhumei; Li, Xiaoqin; Sang, Hongfei; Xia, Wenqing; Huang, Jinyu; Liu, Keqin; Lu, Shan; Jiang, Lin; Shao, Anwen; et al. (Frontiers in Pharmacology, 2022)
Background: Intracranial atherosclerotic stenosis (ICAS) is a common cause of first and recurrent ischemic stroke worldwide. Circular RNAs (circRNA)s have been recently suggested as candidate biomarkers in diagnosing and prognosis of ischemic stroke. A few circRNAs even serve as therapeutic targets that improves neurological function after ischemic stroke. However, the roles of circRNAs in ICAS caused ischemic stroke (ICAS-stroke) have not been fully understood. Therefore, in this study, we attempted to find some clues by investigating the different expression profiles of circRNAs between patients diagnosed with ICAS-stroke and normal control (NC)s. Methods: The OE Biotech Human ceRNA Microarray 4 × 180 K (47, 899 probes) screened circRNAs differentially expressed in peripheral blood in a discovery cohort (five NCs versus five patients with ICAS-stroke). Afterwards, a validation cohort (31 NCs versus 48 patients with ICAS-stroke) was performed by quantitative polymerase chain reaction (qPCR). Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and CircRNA–microRNA-mRNA interaction network was performed to identify potential interactions with microRNAs and pathway-deregulated circRNAs. Results: There were 244 circRNAs differentially expressed in patients diagnosed with ICAS-stroke compared with NCs [fold change (FC) ≥ 2.0 and p-value<0.05]. Among the 244 circRNAs, 5 circRNAs (hsa_circ_0003574, hsa_circ_0010509, hsa_circ_0026628, hsa_circ_0074057, hsa_circ_0016993) were selected for following verification by qPCR. Only hsa_circRNA_0003574 was significantly upregulated in patients than in NCs. GO analysis indicated that predicted target genes involved various biological processes, cellular components, and molecular functions. KEGG analysis showed that many genes were enriched within the arginine and proline metabolism, pyrimidine metabolism, arginine and proline metabolism, lysosome, cytokine-cytokine receptor interaction, and RNA transport. The circRNA-miRNA-mRNA network analysis show the miRNAs that has_circ_0003574 likely interacts with. Conclusion: We observed that hsa_circRNA_0003574 is upregulated in patients with ICAS-stroke compared with NCs, indicating it may be a potential novel biomarker and therapeutic target for ICAS-stroke. In addition, we analyzed the laboratory results and found that homocysteine and glycosylated hemoglobin were elevated among ICAS-stroke patients. The relationship between hsa_circRNA_0003574 and these parameters requires further investigation.